Influência dos estereótipos no processo de avaliação do rendimento escolar do aluno - Carvalho, Jorgelina Pereira de (1980)
The purpose of this study was to examine the influence of stereotype on the learner's evaluation-process. The stereotype was measured through these variable: physical appearence, color and social class. A scale of two points was used. The instruments used were pupil's photographs and school reports judged by a group of teachers, 60 for the photographs and 100 for the school reports. The hypothese tested was: teachers give better grades to the good physical appearence, white and meduim social-class pupils. Eight hundred of Elementary School pupils from Rio de Janeiro County were the subjects of this study. The result of an Analyses of Variance rejected the hypothese. It was also computed a x2 that show that the independ variables are not independente. More studie on this topic were recommended.